Telecommunications infrastructure sharing in Mozambique - Ramos, José Pedro Guedes Simões (2015)
The mobile telecommunications market faces growing challenges throughout the world, especially in the emerging markets on the African continent. The increase of private investment in different areas combined with the need to provide swift, sustainable and efficient answers from an economic and financial perspective has become urgent not only for the desired growth of these markets, but also for their continued development. The market of mobile telecommunications in Mozambique, the country chosen for our study, presents specific challenges in the network coverage in remote and rural areas. In one of the poorest countries in the world, where mobile communications prevail over fixed-network connections, and considering the importance of continuing to attract investment in this sector, without neglecting the least attractive regions from a financial perspective, it is important to study and explore the different technological models which can be implemented. This dissertation identifies the main investment constraints behind the reduced mobile coverage in the least attractive regions in Mozambique and studies the applicability and sustainability of implementing the concept of Neutral Operator associated with infrastructure sharing as one of the solutions to be adopted. It is our purpose that this study may contribute to the development of the mobile telecommunications market in this emerging market and that the Neutral Operator Model may be adapted and improved as needed in order to meet other growth and development objectives for Mozambique.